Whole-Genome Sequencing of Vero E6 (VERO C1008) and Comparative Analysis of Four Vero Cell Sublines - Konishi, Kazuhiro; Yamaji, Toshiyuki; Sakuma, Chisato; Kasai, Fumio; Endo, Toshinori; Kohara, Arihiro; Hanada, Kentaro; Osada, Naoki (Frontiers in Genetics, 2022)
The Vero cell line is an immortalized cell line established from kidney epithelial cells of the African green monkey. A variety of sublines have been established from the original cell line, which display different characteristics. In this study, we determined the whole-genome sequence of Vero E6 (C1008) and performed comparative analysis among Vero JCRB 0111, Vero CCL-81, Vero 76 and Vero E6. Analysis of the copy number changes and loss of heterozygosity revealed that all sublines share a large deletion and loss of heterozygosity on chromosome 12, which harbors type I interferon and CDKN2 gene clusters. We identified a substantial number of genetic differences among the sublines including single nucleotide variants, indels, and copy number variations. The spectrum of single nucleotide variants indicated a close genetic relationship between Vero JCRB0111 and Vero CCL-81, and between Vero 76 and Vero E6, and a considerable genetic gap between the former two and the latter two lines. In contrast, we confirmed the pattern of genomic integration sites of simian endogenous retroviral sequences, which was consistent among the sublines. We identified subline-specific/enriched loss of function and missense variants, which potentially contribute to the differences in response to viral infection among the Vero sublines. In particular, we focused on Vero E6-specific/enriched variants and identified four genes (IL1RAP, TRIM25, RB1CC1, and ATG2A) that contained missense variants specific or enriched in Vero E6. In addition, we found that V739I variants of ACE2, which functions as the receptor for SARS-CoV-2, were heterozygous in Vero JCRB0111, Vero CCL-81, and Vero 76; however, Vero E6 contained the allele with isoleucine, resulting from the loss of one of the X chromosomes.